Pineapples internal quality inspection approaches and its potential effects in Malaysia - Yit, Peng Tan; Kim, Seng Chia; Jam, Mohamad Nur Hakim (Penerbit UTHM, 2020)
Pineapple (Ananas Comosus L. Metil) is a tropical plant under Bromeliaceous family that is grown in American tropics, subtropics, and warmer regions (U. Nations 2012). Pineapple is the second harvest tropical fruit after banana in the world (S. Ndungu 2014). Pineapple has spiny skin that will turn into yellowish brown from green when ripe. Pineapple is a non-climatic fruit that will stop ripping once it is harvested. Pineapple is famous not only because its taste but also its nutrients for health (M. Farid Hossain 2015, p.84). It contains nutriet that can supply suffiecient requirement of calcium, sodium, potassium, fibre, vitamin C, and so on. Those nutrients can help to build up healthy and growth of bone, enhance body immune system, and decrease high blood pressure for body system.